A new metric to help understand Amazon rainforest precipitation. (3rd September 2013) - Schultz, Colin
Abstract : In the Amazon rainforest, the chain of events that turns a small‐scale process like a localized increase in evaporation into a towering storm cloud is long and twisted. To understand the complex dynamics that lead to precipitation and to identify the relative importance of various processes, researchers need uninterrupted observations at high‐resolution time scales over many years. Such observations have traditionally been scarce for tropical continental environments, such as the Amazon, where logistics are difficult.